2020
DOI: 10.1038/s41598-020-68141-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic profiling identifies mediators of anchorage-independent growth and roles of inhibitor of differentiation proteins in invasive lobular carcinoma

Abstract: Invasive lobular carcinoma (ILC) is a histological subtype of breast cancer with distinct molecular and clinical features from the more common subtype invasive ductal carcinoma (IDC). ILC cells exhibit anchorage-independent growth in ultra-low attachment (ULA) suspension cultures, which is largely attributed to the loss of E-cadherin. In addition to anoikis resistance, herein we show that human ILC cell lines exhibit enhanced cell proliferation in ULA cultures as compared to IDC cells. Proteomic comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…ILC is likely have a distinct interaction with the immune microenvironment compared to IDC [ 62 , 63 ]. Additionally, Tasdemir et al, reported that in ultra-low attachment conditions (i.e., requiring anchorage-independence, mimicking metastasis), ILC cell lines were uniquely able to sustain PI3K pathway activation vs. IDC cell lines [ 64 ]. Further mechanistic studies are needed to link biomarkers with PI3K/Akt/mTOR signaling activity to identify precision targets for therapy, i.e., to identify the ideal targeted inhibitor for an individual tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILC is likely have a distinct interaction with the immune microenvironment compared to IDC [ 62 , 63 ]. Additionally, Tasdemir et al, reported that in ultra-low attachment conditions (i.e., requiring anchorage-independence, mimicking metastasis), ILC cell lines were uniquely able to sustain PI3K pathway activation vs. IDC cell lines [ 64 ]. Further mechanistic studies are needed to link biomarkers with PI3K/Akt/mTOR signaling activity to identify precision targets for therapy, i.e., to identify the ideal targeted inhibitor for an individual tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in considering differences in how estrogen drives PI3K/Akt/mTOR signaling in ILC vs. IDC, our RPPA studies included two ILC models (MM134, 44PE) and one IDC model (MCF-7). Proteomics analyses with more models [ 15 , 64 ], accounting for pathway mutations, are needed to understand these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Significance of overlap was calculated using the hypergeometric test in R through the "phyper" function and a total gene count of 20,000. For assessing detachment-induced artifacts in the RHEG gene set, we defined a detachment-induced gene signature as transcripts appearing at least twice among upregulated genes among four luminal breast-cancer lines grown in ultra-low attachment suspension (21). Breast driver genes were obtained from a larger gene list of cancer drivers (22) filtered for tissue of origin.…”
Section: Gene Signature Overlaps With Rhegsmentioning
confidence: 99%
“…Among these RHEGs, 85% were retained when the same analysis was applied to three additional luminal breast cancers (20), suggesting bounds for reliable variability between similar tumors. The shared set of candidates was largely devoid of detachment-induced artifacts (21) and, surprisingly, breast-cancer driver genes (22). Recurrent heterogeneities were instead enriched in the collagen and matricellular constituents of a pancancer epithelial-to-mesenchymal transition (EMT) signature (23).…”
Section: Introductionmentioning
confidence: 99%
“…ILC-like cell lines were reported to have increased proliferation (compared to IDC lines) and induction of PI3K/Akt/mTOR signalling when cultured under Ultra Low Attachment (ULA) conditions, mimicking anoikis-independence. Interestingly, these cells were not sensitive to PI3K/mTOR dual inhibitors [ 115 ].…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 99%